Simulation and Its Role in Training - Samia, Hoda; Khan, Sadaf; Lawrence, Justin; Delaney, Conor P. (Clinics in Colon and Rectal Surgery, 2013)
Despite its short history, surgical simulation has been successfully introduced into surgical residency programs in an effort to augment training. A wide range of simulator types and levels of complexity have proven an effective teaching method for surgical trainees. They have been used for training in areas such as general surgery, urology, gynecology, and ophthalmology among others. Coincident with the introduction of simulators is the need for objective evaluation of skills learned on them, which has led to the development and validation of multiple evaluation tools. This article evaluates the drivers for simulation, types of simulators, training, and evaluation of them especially as it pertains to laparoscopic colorectal surgery.
Keywords: simulator; education; laparoscopic colorectal surgery